Opine catabolism and conjugal transfer of the nopaline Ti plasmid pTiC58 are coordinately regulated by a single repressor. - Beck von Bodman, S (1992)
The Ti plasmids of Agrobacterium tumefaciens are conjugal elements whose transfer is strongly repressed. Transfer is induced by the conjugal opines, a group of unique carbon compounds synthesized in crown gall tumors. The opines also induce Ti plasmid-encoded genes required by the bacteria for opine catabolism. We have cloned and sequenced a gene from the Ti plasmid pTiC58, whose product mediates the opine-dependent regulation of conjugal transfer and catabolism of the conjugal opines, agrocinopines A and B. The gene, accR, is closely linked to the agrocinopine catabolic locus. A spontaneous mutant Ti plasmid, pTiC58Trac, which constitutively expresses conjugal transfer and opine catabolism, was complemented in trans by a clone of wild-type accR. Comparative sequence analysis identified a 5-base-pair deletion close to the 5' end of the mutant accR allele from pTiC58Trac. Analysis of lacZ fusions in conjugal transfer and opine catabolic structural genes demonstrated that the accR-encoded function is a transcriptional repressor. accR can encode a 28-kDa protein. This protein is related to a class of repressor proteins that includes LacR, GutR, DeoR, FucR, and GlpR that regulate sugar catabolic systems in several bacterial genera.